2014
DOI: 10.1007/s11695-014-1178-1
|View full text |Cite
|
Sign up to set email alerts
|

Does Patient Compliance with Follow-up Influence Weight Loss After Gastric Bypass Surgery? A Systematic Review and Meta-Analysis

Abstract: Gastric bypass surgery is an effective intervention to manage morbid obesity. However, there have been suggestions that patients who do not comply to follow-up lose less weight. This study evaluated the influence of patient's follow-up compliance on weight loss post gastric bypass surgery. From the search of MEDLINE and EMBASE, four studies (n = 365) were identified and majority of these studies concluded that compliance with follow-up leads to increased weight loss. Our meta-analysis of these studies found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 23 publications
3
34
0
1
Order By: Relevance
“…%TBWL was 31.7 ± 8.5% and %EBWL was 79.6 ± 28.9% at 12 months compared to pre-surgery weights. The results are similar to previous studies [ 17 , 18 , 19 ]. In addition, several studies described the data in Japanese patients following bariatric surgery [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…%TBWL was 31.7 ± 8.5% and %EBWL was 79.6 ± 28.9% at 12 months compared to pre-surgery weights. The results are similar to previous studies [ 17 , 18 , 19 ]. In addition, several studies described the data in Japanese patients following bariatric surgery [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…In terms of weight loss, a sustained reduction of ≥50% excess weight is considered as a success. Recent meta-analyses and systematic reviews have reported a %EBWL close to 60% one year after a gastric bypass with ranges from 33% to 77% [ 17 , 18 , 19 ]. In the present study, LSG reduced BW in all time periods observed.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulty in achieving lifelong follow‐up after bariatric surgery may also influence the various outcomes and can even be responsible for serious medical complications. It has been established that effective adherence to postoperative follow‐up may have positive effects on weight loss. Late surgical complications may occur during the early years following bariatric surgery and micronutrient deficiency is one of the main long‐term medical adverse effects, especially after malabsorptive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The present study confirmed that there is a low uptake of currently available bariatric apps and also that there is no single, routinely recommended mHealth app among dietitians. Further exploration into apps for these populations is justified because other research has focussed on discrete aspects such as app use in dietetics (18,22,24,25) , apps for bariatric patients (16,17) and reasons for bariatric patients becoming lost to follow-up (9,23,26) .…”
Section: Discussionmentioning
confidence: 99%